2020
DOI: 10.1182/blood-2020-134832
|View full text |Cite
|
Sign up to set email alerts
|

Cytopenia Management in Patients With Newly Diagnosed Acute Myeloid Leukemia Treated With Venetoclax Plus Azacitidine in the VIALE-A Study

Abstract: Background: Patients with acute myeloid leukemia (AML) who are older or ineligible for intensive induction chemotherapy have limited treatment options and poor survival. In the VIALE-A study, venetoclax (Ven) + azacitidine (Aza) improved overall survival and response rates compared with placebo (Pbo) + Aza in older or unfit patients with newly diagnosed AML (DiNardo et al. N Engl J Med. 2020). Although cytopenia is common in AML, Ven+Aza was associated with hematologic adverse events in 83% of patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Composite complete remission was achieved in 66.4% of the patients in the registration study, and the majority of patients (43,4%) achieved CR at the end of the first treatment cycle [12]. In addition a subanalysis of this study showed that up to 77% of patients achieved blast clearance (< 5%) after the first cycle of treatment [35]. Elimination of blasts from the bone marrow, or achieving at least a leukaemia-free morphological status in the case of cytopenia, is an indication for treatment interruption, and its resumption when the morphology recovers (Figure 2).…”
Section: Cytopeniasmentioning
confidence: 63%
See 3 more Smart Citations
“…Composite complete remission was achieved in 66.4% of the patients in the registration study, and the majority of patients (43,4%) achieved CR at the end of the first treatment cycle [12]. In addition a subanalysis of this study showed that up to 77% of patients achieved blast clearance (< 5%) after the first cycle of treatment [35]. Elimination of blasts from the bone marrow, or achieving at least a leukaemia-free morphological status in the case of cytopenia, is an indication for treatment interruption, and its resumption when the morphology recovers (Figure 2).…”
Section: Cytopeniasmentioning
confidence: 63%
“…Among responding patients, the median duration of delay in starting the next cycle was 14 days in the venetoclax plus AZA group and 11 days in the AZA monotherapy group. The dosing intervals during an ongoing cycle were significantly shorter than the next cycle deferring; the median duration of dosing intervals during a treatment cycle was 2 days in the venetoclax and AZA group and 1 day in the AZA group [35]. G-CSF should be considered for the treatment of post-remission neutropenia.…”
Section: Cytopeniasmentioning
confidence: 92%
See 2 more Smart Citations
“…Analysis of OS showed no difference in outcome for those switching immediately to 21-day VEN, compared with those persisting with a 28-day schedule. 20 To guide decision making, we recommend a marrow assessment on day 21 and ceasing VEN if blast clearance is demonstrated. A VEN-free interval enables neutrophil and platelet recovery, for example, to CR with partial hematologic recovery, before commencing the next cycle.…”
Section: Optimizing Venetoclax Dosing Durationmentioning
confidence: 99%